Antimicrobial and antidiabetic potential of synbiotic fermented milk: A functional dairy product. (4th September 2018) - Shafi, Afshan; Naeem Raja, Haider; Farooq, Umar; Akram, Kashif; Hayat, Zafar; Naz, Ambreen; Nadeem, Hafiz Rehan
Abstract : The current study was based on evaluation of the therapeutic potential (antimicrobial and antidiabetic) of a synbiotic fermented milk product developed by optimising levels of the prebiotic ingredients (fructooligosaccharide and isomaltooligosaccharide). The maximum growth rate (0.27 ± 0.21a cfu/mL) of Lactobacillus acidophilus ATCC ® 4357 ™ was observed with 2.345–2.445% of fructooligosaccharide and 2.53–2.62% of isomaltooligosaccharide. Significant antimicrobial potential of the synbiotic fermented milk was observed against Escherichia coli and Staphylococcus aureus due to the addition of prebiotics. Similarly, the final product also showed 62.9%, 71.5% and 57.0% reduction in blood glucose, urea and creatinine levels, respectively, of diabetic rabbits, when supplemented with 6% of the synbiotic fermented milk. A synbiotic fermented milk product with significant therapeutic potential could be developed using fructooligosaccharide and isomaltooligosaccharide as prebiotic ingredients.